Gluteal muscle inhibition: Consequences of patellofemoral pain?. (May 2019) - Glaviano, Neal R.; Bazett-Jones, David M.; Norte, Grant
Abstract: Muscle weakness is a common impairment in females with patellofemoral pain (PFP), clinically seen in both the quadriceps and gluteal muscles. These weaknesses have been suggested to result in poor movement patterns, which results in the clinical presentation of pain due to increased stress on the patellofemoral joint. While quadriceps weakness have been identified as a risk factor for the development of PFP, prospective studies have not found gluteal muscle weakness to be a risk factor. Therefore, gluteal muscle weakness may in fact be a consequence of PFP. This muscle weakness is often combated with traditional strengthening programs. These interventions improve both short-term subjective function and improve strength, yet their relationship to long-term outcomes are less than optimal. Strength training of the gluteals also does not transition to improved movement patterns in this population. The presence of hip muscle inhibition may be the explanation for both poor long-term function and altered movement patterns. Assessment methods for muscle inhibition have been studied in the quadriceps, commonly conducted with the superimposed burst technique to calculate an activation ratio. The use of this method may be used on the gluteus medius and gluteus maximus muscles to determine if inhibition of the hip musculature is present in females with PFP. This knowledge would provide clinicians with a more complete picture of muscle dysfunction and lead to a paradigm shift in clinical treatment strategies for this chronic condition. We hypothesize that muscle inhibition is present in the gluteal muscles of females with PFP compared to healthy controls and it is associated with both decreased subjective function and longer duration of symptoms.